BENTUK GAYA BAHASA KOMUNIKASI FACEBOOK KOMUNITAS SENIMAN LAKI-LAKI - Muh. Irfan Mukhlishin; Maryaeni Maryaeni; Yuni Pratiwi (Graduate School of Universitas Negeri Malang, 2016)
The use of increasingly diverse language, it is because they want or do not want the language we use will definitely be contaminated with the language of all regions in Indonesia and even discuss international languages. Therefore this article seeks to know the style of male language in communication through social media facebook, especially for the community of artists in Malang. In particular how the shape and meaning of language style male artist community in facebook? Style of language used male artist in the city of Malang is a stylistic comparison that is widely used is the